Constitutional Challenges in Formulating the National Education System Bill from the Perspective of Citizens’ Constitutional Right to Education - Popy Rakhmawaty; Azis Budianto (Yayasan Cendekia Gagayunan Indonesia, 2025)
Article 31 of the Republic of Indonesia's 1945 Constitution clearly guarantees the right to education. All citizens must get high-quality, just, and equal education from the state. In this regard, the National Education System Bill (RUU Sisdiknas) is being drafted as a calculated move to update the country's educational legislation, which has been regulated in various sectoral laws. This study aims to analyze the conformity of the formulation of the RUU Sisdiknas with the principle of citizens' constitutional rights to education, as well as to identify legal problems that arise in the process and substance of its formulation. With a statutory, conceptual, and comparative perspective, this study employs a normative juridical method. The analysis's findings show that while the RUU Sisdiknas makes an effort to incorporate different educational laws, there are a number of clauses that could jeopardize the right to education, especially when it comes to the removal of particular clauses pertaining to the teaching profession and basic education funding. In addition, the less participatory formulation process raises questions about the public legitimacy of the draft. Therefore, harmonization of norms is necessary to ensure that the National Education System Bill truly aligns with the constitutional mandate, human rights principles, and the state's goal of improving the nation's life.